Menjaga Kelestarian Waduk Sermo - Lukisworo, Agustinus Aryo (Jurnal Atma Inovasia, 2021)
In the KKN Periode 79 of Universitas Atma Jaya Yogyakarta, Kelompok 4 (the Fourth group) of Unit A was assigned to the Hargowilis Village, Kokap, Kulon Progo, Daerah Istimewa Yogyakarta. Due to the spread of Covid-19 pandemic, this period of KKN was held online. Therefore all of this KKN period programs was written upon secondary data. Based on online inquiries, Kelompok 4 has found that Hargowilis has interesting natural resources, and one of it was called Waduk Sermo. Moreover, our findings shows that Waduk Sermo has a crucial problem regarding to waste. Along with becoming an issue for Waduk Sermo’ attractiveness, it also potent to raise ecological problem, especially related to soil fertility. Thus we decided to propose waste management program called 3R that are Reduce, Reuse, and Recycle. We hope that the implementation of this waste processing, aside with increasing environmental hygiene and public health, will also lead to the economic development of Hargowilis.